The Retention of fresh graduated employees in Kuala Lumpur Hotels - Chaichi, Kamelia; Fouad Salem, Suha (Opción, 2019)
This paper aims to answer some questions about perception and factors for retention of hospitality and tourism graduated individuals who are employees in the hotel industry in Kuala Lumpur. Due to the exploratory nature of this study, a qualitative research method is conducted. As a result, organizations with good politics make generous profits by providing the proper level of privacy, which promotes long-term commitment to the organization. In conclusion, since employee retention is extremely essential for the growth of the hospitality and tourism organization such as hotels, managers and supervisors need to know how to motivate their employees.